Analisis fungsi Perencanaan Pengembangan Badan Usaha Milik Desa ( Bumdes) ( Studi Di Desa Tawangargo Kecamatan Karangploso Kabupaten Malang) - Rasti Nanda Sari (Dialektika Publik, 2022)
With the enactment of Law Number 6 of 2014 concerning villages, it is hoped that all interests and village development can be better managed. Village residents and government have full authority and village managers plus assets and potential and are responsible for the activities carried out in village government development. In this type of qualitative research, with primary data sources and secondary data sources, data collection techniques are observation, interviews, and documentation, sampling technique using purposive sampling, systematically data obtained from interviews and documentation by describing into units, choosing which one will be studied and make conclusions, as well as data validity techniques with triangulation techniques. The study results prove that from the planning aspect, the village government is increasing community participation in village development, and the function of the bundle's program, which can be called, is still lacking. From the aspect of accountability, the bundles' story is still lacking. The supporting and inhibiting factors for bundles development planning and community participation in developing the bundle's management program in Tawangargo village are the inactive capacity of community resources,information problems, and institutions that have not been utilized optimally